"Pioneer" images. From Space Art to Space Advertising (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2018)
In this article are defined and discusses the “pioneer” images as images drawn to foster the conquest of new spaces, that are both mental and cosmic. They are produced by both public and private US space agencies, in order to raise the awareness of the public opinion and to prepare it for new ways of living and new habitable worlds. It will highlight the use of graphic languages within the aerospace agencies projects, where art and science collaborate creating effective informative and persuasive images. In particular, this article focuses on the NASA and SpaceX visual communication campaigns for the interplanetary exploration and colonisation, that have been widely spread over the last few years thanks to the use of the web and of the social networks.